Welding ANALISA PENGARUH VARIASI ARUS PENGELASAN KOMBINASI SMAW DAN GTAW TERHADAP PENGUJIAN KEKERASAN, KEKUATAN IMPAK SERTA PENGAMATAN STRUKTUR MIKRO PADA BAJA JIS SS400 - Semuel Desmon (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2022)
Welded joints are a very important part in a construction material in which there are parameters that determine the quality of the strength and toughness of the material in accepting certain loads, to get the maximum quality the writer tries to raise the theme of combination welding of Shielded Metal Arc Welding (SMAW) and Gas Tungsten Arc Welding (GTAW) with the classification of current variations in the welding method SMAW 95 A (low current), 110 A (medium current), and 125 A (high current), while in GTAW welding method uses a current of 70 A, on the JIS SS400 steel plate material with 10 mm thickness. The microstructure observation was carried out at 4 points of HAZ SMAW, HAZ GTAW, weld metal SMAW, and weld metal GTAW as the parts that were heat affected zone. The hardness test results that have the highest hardness value on the based metal is plate 1 with a value of 78.5 HRB, on the left HAZ SMAW is plate 3 with a value of 78.66 HRB, on the left HAZ GTAW is plate 3 with a value of 77.16 HRB , on SMAW weld metal is plate 1 with a value of 82.16 HRB, on GTAW weld metal is plate 1 with a value of 83.66 HRB, on the right HAZ SMAW is plate 3 with a value of 78.33 HRB, and on the right HAZ GTAW is plate 3 with a value of 77.83 HRB. In the impact test plate 1 has an impact strength value of 130.8 J, plate 2 is 139.3 J, and plate 3 is 103 J.